Koreografi Tari Piring Gelas Di Sanggar Kupek Beghaes - Siska Ayumi; Eva Riyanti; Suherni Suherni (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research discusses the choreography of Piring Gelas Dance which developed in Sanggar Kupek Beghaes, North Musi Rawas Regency, South Sumatra Province. This dance is a traditional performance art that depicts the courage and determination of Musi Rawas women in maintaining religious and cultural values through the attraction of walking on a pile of plates and glasses. This research uses descriptive qualitative method with observation, interview, and documentation techniques. The results showed that the choreography of Glass Plate Dance consists of nine main elements: dancers, movements, music, costumes and makeup, floor patterns, performance venues, properties, lighting, and performance techniques. The main dancer must be a girl called dehe, and accompanied by two dayang dancers who are in charge of arranging a pyramid of plates and glasses. Core movements include greetings, glances, turns, transitions, and climbing the plate. The technique of walking on the plate pyramid requires great balance and poise. The main property is 16 glass plates and 6 glasses arranged into a two-level pyramid. This dance is performed in open and closed spaces and holds a deep philosophy of patience, precision, and female elegance. This research emphasizes the importance of preserving traditional dance as a local cultural heritage that is full of educational and aesthetic values.